Relationship of physical activity and healthy eating with mortality and incident heart failure among community‐dwelling older adults with normal body mass index. (7th April 2015) - Abdelmawgoud, Ahmed; Brown, Cynthia J.; Sui, Xuemei; Fonarow, Gregg C.; Kokkinos, Peter F.; Bittner, Vera; Aronow, Wilbert S.; Kheirbek, Raya E.; Fletcher, Ross D.; Blair, Steven N.; Ahmed, Ali
Abstract Aims Normal body mass index (BMI) is associated with lower mortality and may be achieved by physical activity (PA), healthy eating (HE), or both. We examined the association of PA and HE with mortality and incident heart failure (HF) among 2040 community‐dwelling older adults aged ≥ 65 years with baseline BMI 18.5 to 24.99 kg/m2 during 13 years of follow‐up in the Cardiovascular Health Study. Methods and results Baseline PA was defined as ≥500 weekly metabolic equivalent task‐minutes and HE as ≥5 daily servings of vegetable and fruit intake. Participants were categorized into four groups: (i) PA−/HE− (n = 384); (ii) PA−/HE+ (n = 162); (iii) PA+/HE− (n = 992); and (iv) PA+/HE+ (n = 502). Participants had a mean age of 74 (±6) years, mean BMI of 22.6 (±1.5) kg/m2, 61% were women, and 4% African American. Compared with PA−/HE−, age‐sex‐race‐adjusted hazard ratios and 95% confidence intervals for all‐cause mortality for PA−/HE+, PA+/HE−, and PA+/HE+ groups were 0.96 (0.76–1.21), 0.61 (0.52–0.71), and 0.62 (0.52–0.75), respectively. These associations remained unchanged after multivariable adjustment and were similar for cardiovascular and non‐cardiovascular mortalities. Respective demographic‐adjusted hazard ratios (95% confidence intervals) for incident HF among 1954 participants without baseline HF were 1.21 (0.81–1.81), 0.71 (0.54–0.94), and 0.71 (0.51–0.98). These latter associations lost significance after multivariable adjustment. Conclusion Among community‐dwelling older adults with normal BMI, physical activity, regardless of healthy eating, was associated with lower risk of mortality and incident HF, but healthy eating had no similar protective association in this cohort.